Does unilateral surgically assisted rapid maxillary expansion (SARME) lead to perinasal asymmetry? - YILMAZ, HANİFE NURAY (URBAN & VOGEL, 2022)
Objective True unilateral posterior crossbite (TUPC) requires unilateral expansion to prevent nonocclusion at the noncrossbite (NC) side. The recommended osteotomies for TUPC after sutural closure are anterior, lateral, and posterior osteotomies only on the crossbite (C) side and median osteotomy of the midpalatal suture, i.e., unilateral surgically assisted rapid maxillary expansion (SARME). The goal was to assess airway and perinasal soft tissue outcomes after SARME. Methods Data from 16 patients (8 males, 8 females; mean age 18.38 +/- 1.45 years) were retrospectively assessed after unilateral SARME. The expansion (twice daily: 0.5 mm/day) and retention periods comprised 3 weeks and 6 months, respectively. Stereophotogrammetric images were used for soft tissue assessment; cone beam computed tomography (CBCT) was used to evaluate the anterior nasal airway. Statistical analyses were performed. Results Using linear measurements, soft tissue distances of the alar base and alare to midsagittal plane (MSP) were significantly increased on the C side. A significant decrease was observed for the distance from the lower nostril point to the MSP on the NC side compared to a significant increase on the C side. Comparing the C and NC sides, the changes were significantly higher on the C side for all parameters except the upper nostril point to the MSP distance. Cheek volume was significantly higher on the C side. Volume changes of the anterior nasal airway (ANA) were significantly increased on the C side, but volume changes between NC and C were not significantly different. Conclusions Unilateral SARME led to significant expansion of ANA on the C side, but did not lead to asymmetry in the nasal region or have adverse effects on the airway or perinasal soft tissues. Thus, this novel treatment method may be useful in the treatment of patients with TUPC.
Keywords: True unilateral posterior crossbite; Orthognathic surgical procedures; Unilateral expansion; Malocclusion; Maxillary osteotomy; SOFT-TISSUE CHANGES; BEAM COMPUTED-TOMOGRAPHY; 3-DIMENSIONAL EVALUATION; OROFACIAL REGION; TOOTH-BORNE; AIRWAY; ACCURACY